BS EN 438-7. High-pressure decorative laminates (HPL). Sheets based on thermosetting resins (Usually called Laminates). Part 7. Compact laminate and HPL composite panels for internal and external wall and ceiling finishes (2nd September 2019) - British Standards Institution,
No abstract available